The Marginalized Mudbloods and The Squibs of Hogwarts: A Study of ‘Disability’ Through A Medium of J.K. Rowling’s Harry Potter Series - Basu, Debangana; Mukherjee, Paromita (Litinfinite Journal, 2023)
It was not until the 20th century that disability studies were initialized in the West with some of the seminal works of scholars like Michel Foucault and Erving Goffman. The disability studies essentially gave a voice to those people who were denied social justice, and it was not only considered as a medical problem anymore; rather it was a major social issue. Apart from some of the major classics, if one can take a look inside the pop culture texts, then J.K. Rowling’s Harry Potter series would present before us an array of such issues concerning marginalized disabled people. In this paper, we would like to show the unfortunate treatment of such ‘disabled’ people in the magical world of Hogwarts, keeping in parallel view the sorrowful situation of our real world as well, based on the theoretical grounds laid down by Foucault and Goffman. Also, we intend to shed some light on the identity formation of the disabled group, which is directly linked with gender, race, and class. It is also our intention to reflect on the fact that disability is something which is not to be “fixed” but rather embraced and normalized, to achieve an egalitarian society.